2019
DOI: 10.3390/min9070425
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Modeling of Silicate and Carbonate Sulfidation under Lithospheric Mantle P,T-Parameters

Abstract: : Interactions of mantle silicates with subducted carbonates, sulfides, and sulfur-rich fluids are experimentally simulated in the olivine-ankerite-sulfur and olivine-ankerite-pyrite systems using a multi-anvil high-pressure split-sphere apparatus at 6.3 GPa and range of 1050–1550 °C. Recrystallization of Fe,Ni-bearing olivine and ankerite in a sulfur melt was found to be accompanied by sulfidation of olivine and carbonate, involving partial extraction of metals, carbon, and oxygen into the melt, followed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Thermodynamic calculations [48] show that, under subduction conditions, pyrite is stable up to the parameters of the eclogite facies (pressure~5-6 GPa, depth~150-180 km), at greater depths, pyrite undergoes incongruent melting, with the formation of a sulfur melt and pyrrhotite. In this study, as well as in [43], we experimentally confirmed and supplemented the existing assumption of Tomkins and Evans [48] that under high-pressure conditions, a significant part of the subducted pyrite gradually transforms into pyrrhotite as a result of reactions Fe,Mg silicates or Fe-bearing oxides according to the schematic reaction FeS 2 + (Fe,Mg)O in silicates = 2FeS + MgO in silicates . Our data indicate that the enrichment of pyrite with iron and its transition to pyrrhotite can occur when interacting with iron-bearing carbonates, for example, with ankerite, according to a similar reaction.…”
Section: Implications Of the Results Of Ankerite-pyrite Interaction To Graphite Formation Via Ankerite Sulfidation In The Lithospheric Masupporting
confidence: 84%
See 1 more Smart Citation
“…Thermodynamic calculations [48] show that, under subduction conditions, pyrite is stable up to the parameters of the eclogite facies (pressure~5-6 GPa, depth~150-180 km), at greater depths, pyrite undergoes incongruent melting, with the formation of a sulfur melt and pyrrhotite. In this study, as well as in [43], we experimentally confirmed and supplemented the existing assumption of Tomkins and Evans [48] that under high-pressure conditions, a significant part of the subducted pyrite gradually transforms into pyrrhotite as a result of reactions Fe,Mg silicates or Fe-bearing oxides according to the schematic reaction FeS 2 + (Fe,Mg)O in silicates = 2FeS + MgO in silicates . Our data indicate that the enrichment of pyrite with iron and its transition to pyrrhotite can occur when interacting with iron-bearing carbonates, for example, with ankerite, according to a similar reaction.…”
Section: Implications Of the Results Of Ankerite-pyrite Interaction To Graphite Formation Via Ankerite Sulfidation In The Lithospheric Masupporting
confidence: 84%
“…Despite the fact that the fundamental possibility of the formation of diamond and graphite by reduction of carbonate/CO 2 -fluid with sulfides or sulfide melts has already been experimentally demonstrated, there are still a number of unresolved issues in this direction. In particular, our recent experimental studies in multicomponent Fe,Ni-olivineankerite-sulfur and Fe,Ni-olivine-ankerite-pyrite systems [43], aimed at modeling the reactions of silicates and carbonates sulfidation, showed the possibility of crystallization of elemental carbon (graphite) in these processes. However, due to the complexity of the studied systems, a detailed reconstruction of the formation processes of elemental carbon phases during sulfidation of FeO-bearing carbonates was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…The two complete datasets for trace chalcophile/siderophile elements contents available for eclogitic diamonds are those of Aulbach et al predicted by models of diamond production involving interaction between oxidized carbonatebearing subducted slabs and reduced metal-saturated mantle rocks (see reviews by Cartigny, 2005 ;Stachel & Harris, 2008;Shirey et al, 2013) or between reduced oceanic crust and oxidizing CO 2 -rich fluids, if, as pointed out by Aulbach et al (2017Aulbach et al ( , 2019, the Archaean oceanic crust had highly reduced compositions, markedly below carbonate stability. Zdrokov et al (2019) reproduced the highly metal-deficient pyrrhotite compositions in their experiments on diamond production involving carbonate melts. By contrast, taken altogether, our data suggest an unusually important contribution of reducing sedimentary component for Beni Bousera graphite-garnet clinopyroxenites, as required by their high BMS modal abundance, their strongly fractionated S/Se, their diluted Ni content, coupled with troilite composition.…”
Section: Comparison With Diamond-hosted Bms Inclusionsmentioning
confidence: 83%
“…Also, BMS inclusions are so common in eclogitic diamonds that they are considered to be involved in diamond genesis, acting either as reducing agents enhancing precipitation of diamonds from oxidized carbon-bearing fluids, as nucleii for diamond crystals, or as "catalysts" enhancing carbon dissolution and precipitation from sulphide melts (e.g. Luque et al, 1998;Stachel & Harris, 2008;Shirey et al, 2013;Palyanov et al, 2007;Bataleva et al, 2019;Zdrokov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%